Experimental research of the influence of the power plans on PC performance and energy consumption - Вдовитченко, Александр Валерьевич (Eastern-European Journal of Enterprise Technologies, 2015)
The features of energy consumption in the field of information technology were considered, the impact of information technology on the environment was analyzed. The tasks that form a new direction – green information technology were singled out. The existing programs and standards in the field of energy management of computer and peripheral devices were given. Experimental research by energy consumption criteria and computer performance rating using available performance evaluation tool PCMark 7 (which allows to estimate the system properties as a whole, and for particular applications) and energy profiler Joulemeter (which allows to estimate the energy spent by devices and processes) were carried out. Based on the resulting data, the analysis was performed using the mathematical statistics and correlation-regression analysis methods and the results were obtained, the transition of the PC energy consumption from the economical plan to maximum performance mode leads to: – an increase in the energy spent by the CPU on calculations in the test mode by 40%; – a reduction of the testing time by 20%; – an increase of the performance rating (Scope) according to the PCMark 7 results by 35%. It was emphasized that when evaluating energy-consuming characteristics of individual applications (text editors, web-surfing software), performance and energy consumption increase by 2 times. The choice of power supply modes depends on the applied task solved and it can be considered a base for further construction of automatic control systems of the computer performance and energy consumption balance to achieve maximum efficiency.